Personalization of loco-regional care for primary breast cancer patients (part 2). (May 2015) - Toi, Masakazu; Winer, Eric P; Benson, John R; Inamoto, Takashi; Forbes, John F; von Minckwitz, Gunter; Robertson, John FR; Grobmyer, Stephen R; Jatoi, Ismail; Sasano, Hironobu; Kunkler, Ian; Ho, Alice Y; et al.
ABSTRACT : Kyoto Breast Cancer Consensus Conference, Kyoto, Japan, 18–20 February 2014 The loco-regional management of breast cancer is increasingly complex with application of primary systemic therapies, oncoplastic techniques and genetic testing for breast cancer susceptibility. Personalization of loco-regional treatment is integral to optimization of breast cancer care. Clinical and pathological tumor stage, biological features and host factors influence loco-regional treatment strategies and extent of surgical procedures. Key issues including axillary staging, axillary treatment, radiation therapy, primary systemic therapy (PST), preoperative hormonal therapy and genetic predisposition were identified and discussed at the Kyoto Breast Cancer Consensus Conference (KBCCC2014). In the second of a two part conference scene, consensus recommendations for radiation treatment, primary systemic therapies and management of genetic predisposition are reported and focus on the following topics: influence of both clinical response to PST and stage at presentation on recommendations for postmastectomy radiotherapy; use of regional nodal irradiation in selected node-positive patients and those with adverse pathological factors; extent of surgical resection following downstaging of tumors with PST; use of preoperative hormonal therapy in premenopausal women with larger, node-negative luminal A-like tumors and managing increasing demands for contralateral prophylactic mastectomy in patients with a unilateral sporadic breast cancer.